Trust-based secure routing against lethal behavior of nodes in wireless adhoc network - Jyoti Neeli; N. K. Cauvery (Institute of Advanced Engineering and Science, 2020)
Offering a secure communication in wireless adhoc network is yet an open-end problem irrespective of archives of existing literatures towards security enhancement. Inclination towards solving specific forms of attack in adhoc network is majorly seen as an existing trend which lowers the applicability of existing security solution while application environment or attack scenario is changed. Therefore, the proposed system implements an analytical secure routing modeling which performs consistent monitoring of the malicious behaviour of its neighboring node and formulates decision towards secure routing by the source nodes. Harnessing the potential ofconceptual probabilistic modeling, the proposed system is capable as well as applicable for resisting maximum number / types of threats in wireless network. The study outcome show proposed scheme offer better performance in contrast to existing secure routing scheme.